Phosphate homeostasis and genetic mutations of familial hypophosphatemic rickets - Razali, Nurul Nadirah; Ting, Tzer Hwu; Karrupiah, Thilakavathy (Walter de Gruyter, 2015)
Hypophosphatemic rickets (HR) is a syndrome of hypophosphatemia and rickets that resembles vitamin D deficiency, which is caused by malfunction of renal tubules in phosphate reabsorption. Phosphate is an essential mineral, which is important for bone and tooth structure. It is regulated by parathyroid hormone, 1,25-dihydroxyvitamin D and fibroblast-growth-factor 23 (FGF23). X-linked hypophosphatemia (XLH), autosomal dominant HR (ADHR), and autosomal recessive HR (ARHR) are examples of hereditary forms of HR, which are mainly caused by mutations in the phosphate regulating endopeptidase homolog, X-linked (PHEX), FGF23, and, dentin matrix protein-1 (DMP1) and ecto-nucleotide pyro phosphatase/phosphodiesterase 1 (ENPP1) genes, respectively. Mutations in these genes are believed to cause elevation of circulating FGF23 protein. Increase in FGF23 disrupts phosphate homeostasis, leading to HR. This review aims to summarize phosphate homeostasis and focuses on the genes and mutations related to XLH, ADHR, and ARHR. A compilation of XLH mutation hotspots based on the PHEX gene database and mutations found in the FGF23, DMP1, and ENPP1 genes are also made available in this review.